2004
DOI: 10.3171/foc.2004.16.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary management of prolactinomas

Abstract: Prolactin-secreting pituitary adenomas—prolactinomas—are the most common type of functional pituitary tumor. Treatment of hyperprolactinemia is indicated because of the consequences of infertility, gonadal dysfunction, and osteoporosis. Making the correct diagnosis is important because the first line of therapy is medical management with dopamine agonists. Medical therapy is effective in normalizing prolactin levels in more than 90% of patients, but long-term treatment may be required in some patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 155 publications
(118 reference statements)
1
45
0
2
Order By: Relevance
“…In contrast, most authors agree to consider surgery as a second choice of treatment for patients with prolactinoma at any age, when DAs prove to be inefficient or badly tolerated, even though some advocate TSS for microprolactinomas when conditions for definitive cure are fulfilled (57). However, surgery for microprolactinomas would be highly questionable in the elderly, since hyperprolactinaemia itself is poorly symptomatic.…”
Section: Surgerymentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, most authors agree to consider surgery as a second choice of treatment for patients with prolactinoma at any age, when DAs prove to be inefficient or badly tolerated, even though some advocate TSS for microprolactinomas when conditions for definitive cure are fulfilled (57). However, surgery for microprolactinomas would be highly questionable in the elderly, since hyperprolactinaemia itself is poorly symptomatic.…”
Section: Surgerymentioning
confidence: 88%
“…However, surgery for microprolactinomas would be highly questionable in the elderly, since hyperprolactinaemia itself is poorly symptomatic. On the other hand, macroprolactinomas are poorly controlled by TSS (57), and this seems to be especially true in the elderly (4,6,7). We have thus progressively abandoned TSS as a debulking option in these patients, and further limited surgical indications to resistant macroprolactinomas with visual defects or clear radiological evidence of tumour progression.…”
Section: Surgerymentioning
confidence: 99%
“…In our study, no important influence of preoperative DA administration on surgical outcomes was found. Furthermore, most studies including the present data found that tumor cytoreduction after surgery typically elevates the responsiveness of DA and hence decreases the required dosage, even if surgery is not curative (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Prolactinomas are the most common hormone-secreting pituitary tumors, accounting for approximately 40% of all pituitary tumors and 50-60% of all functional pituitary tumors [1][2][3]. Patients typically present with clinical features of hyperprolactinemia, including gonadal dysfunction, amenorrhea and galactorrhea.…”
Section: Introductionmentioning
confidence: 99%